Exploring the role of context in emerging adults' experiences of occupational possibilities and occupational choice in a community in the Western Cape: a narrative inquiry - Wicht, Minkateko (Department of Health and Rehabilitation Sciences, 2025)
Introduction: Occupational therapists recognise that health and wellbeing are inextricably linked to people's occupations. Many emerging adults within the Western Cape, South Africa, are experiencing numerous social, economic, and educational challenges which may constrain their occupational engagement and negatively influence their transition into adulthood. Understanding how contexts shape the occupational possibilities and occupational choice of emerging adults will allow occupational therapists, who work with emerging adults in constraining contexts, to better support their transition into adulthood, promote meaningful and purposeful occupational engagement and ultimately enable health and wellbeing. Research Aim: The aim of this study was to explore how living in a community within Bredasdorp, Western Cape, shapes the experience of occupational possibilities and occupational choice of emerging adults aged between 18 and 25 years. Research Design: This qualitative study was informed by the social constructivist/interpretivist paradigm and used a narrative inquiry design. It utilized a transactional perspective of occupation and Laliberte-Rudman's theory of occupational possibilities and Galvaan's theory of occupational choice as the guiding theoretical frameworks. Five participants were recruited, through purposive sampling methods, with the assistance of a community-based organisation. Photovoice methods were used to generate visual data for interviews. Narrative data was then generated through two in-depth unstructured narrative interviews per participant. Data Analysis: Data was analysed using both analyses of narratives and narrative analyses methods and included three levels of analysis, namely, narrative story writing; coding, editing and member-checking of narrative stories; and individual case analysis and cross-case analysis. Findings: One overarching theme emerged from the analysis which showed that occupational possibilities and occupational choice were not dependent on either individual agency or contexts but rather resulted from an interplay between the two. Conclusion: The participants' contexts played an integral role in shaping their occupational possibilities and occupational choices and influenced their health and wellbeing by supporting or constraining a range of available choices, resources, opportunities and possibilities. This study also found that there was a transactional relationship between occupational possibilities and occupational choice. Lastly, there was some fit between the theory of emerging adulthood and the participants' experiences within their contexts.